(untitled) (Nóema, 2023)
The goal of the essay is to understand the dynamics of the processes that have affected philosophy as a complex institutional field, especially in relation to the rapid processes of change that have taken place in universities in Western countries over the last few decades. After introducing the concept of institution, the contribution investigates the backdrop against which the ongoing process of redefining the relationships between knowledge in the academic context and the way in which knowledge practices that characterize our societies today influence and inform, while being simultaneously influenced by, university institutions. In conclusion, the essay explores the institutional conditions for transdisciplinary pathways that can inhabit the ongoing processes through a new «ethics of knowledge», by proposing a political agenda that can also contribute to rethinking philosophy as an institution.